the Effect of Application Big Data on Employees, Vision and Mission of Companies in Indonesia - Muhammad Fahrizal Hasibuan (Journal Research of Social Science, Economics, and Management, 2022)
A company is always committed to tracking the correct way of working and scheduling to ensure quality and quantity. This study aims to determine the effect of big data on employees, vision and mission of companies in Indonesia. The type of research used is literature study. A systematic, unambiguous and repeatable method for identifying, discovering, and synthesizing research and the ideas it generates. This research results that big data is very influential on employees in order to improve the quality of human resources, as well as the vision and mission of a company. Big data has the benefits of increasing the growth and profit potential of a company, being able to compete with big businesses, increasing sales and employee loyalty, ensuring the right employee recruitment according to the job desk, and saving costs.